2022
DOI: 10.3390/plants11101290
|View full text |Cite
|
Sign up to set email alerts
|

Research Advancement in Grassland Ecosystem Vulnerability and Ecological Resilience and Its Inspiration for Improving Grassland Ecosystem Services in the Karst Desertification Control

Abstract: Karst desertification control of grasslands balances the ecological and economic benefits of ecological restoration and rural ecological animal husbandry development. In the context of global changes and intensified human activities, the fragility of grassland ecosystems under karst desertification control is becoming increasingly evident, and enhancing the ecological resilience and ecosystem services of grasslands is an issue that urgently needs to be addressed. In this paper, the CNKI literature, WOS core da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 102 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The issue of the low stability of grassland ecosystems, can be explored through the mechanisms regulating the stability of grassland ecosystems, identify and quantify the factors affecting the stability of grassland ecosystems, select grass species suitable for local conditions, increase the diversity of grassland species, improve the resilience of grassland ecosystems, enhance ecological stability, and further promote the process of grassland ecological restoration, so as to reduce the ecological vulnerability of grassland and enhance the resilience and stability of grassland ecosystems [ 229 ].…”
Section: Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The issue of the low stability of grassland ecosystems, can be explored through the mechanisms regulating the stability of grassland ecosystems, identify and quantify the factors affecting the stability of grassland ecosystems, select grass species suitable for local conditions, increase the diversity of grassland species, improve the resilience of grassland ecosystems, enhance ecological stability, and further promote the process of grassland ecological restoration, so as to reduce the ecological vulnerability of grassland and enhance the resilience and stability of grassland ecosystems [ 229 ].…”
Section: Prospectsmentioning
confidence: 99%
“…Karst areas are very fragile and prone to ecological degradation due to their unique binary three-dimensional geological structure, of which karst desertification is an extreme manifestation of ecological degradation [ 229 ]. In the past 30 years, the KDC in southern China has achieved remarkable results in ecological environment and ecological restoration, but there is an urgent need to improve the stability of the KDC ecosystem and ecosystem service function [ 52 , 235 ].…”
Section: Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecosystem Service Capacity of Grasslands for KDC 4.2.1. The Current Status of Grassland Ecosystem for KDC Karst areas are very fragile and prone to ecological degradation due to their unique binary three-dimensional geological structure, of which karst desertification is an extreme manifestation of ecological degradation [229]. In the past 30 years, the KDC in southern China has achieved remarkable results in ecological environment and ecological restoration, but there is an urgent need to improve the stability of the KDC ecosystem and ecosystem service function [52,235].…”
Section: The Current Status Of Grassland Ecosystem For Kdc and Inspir...mentioning
confidence: 99%
“…The nutrient elements of plants, soil and microorganisms are coupled in the ecosystem process, but it is difficult to reveal the ecosystem process and quality change only through the study of nutrient elements, while C:N:P ratios can reflect the functional characteristics of nutrient use efficiency and nutrient limitation [9][10][11]. Currently, there are numerous studies on the ecological stoichiometry characteristics of degraded ecosystems, involving a wide range of research areas and objects [12][13][14][15][16], and these studies showed that there were certain differences in C, N, and P concentrations and ecological stoichiometry of plant-soil-microorganism systems in different regions, habitats and vegetation restoration measures. Vegetation restoration measures are one of the important factors affecting the C, N and P cycle of plant-soil-microorganism systems [17].…”
Section: Introductionmentioning
confidence: 99%